The Impact of the New Student Orientation Program on the Adaptation Process and Academic Performance - Mohzana Mohzana (Yayasan Adra Karima Hubbi, 2024)
Background. The process of adapting new students to an academic environment can be a serious challenge. The new student orientation program is one effort to facilitate their adaptation. Purpose. The New Student Orientation Program (POMB) is a critical initiative in helping students cope with significant environmental changes. Methods. This research aims to evaluate the effectiveness of the new student orientation program in facilitating their adaptation process and its impact on academic performance. Apart from that, to find out the factors that influence the level of successful adaptation of new students will also be analyzed. This research method uses quantitative and qualitative approaches. A survey will be conducted to collect data regarding student perceptions of the orientation program. In addition, in-depth interviews with students and program organizing staff will be conducted to gain a deeper understanding. Results The research results show that the new student orientation program has a positive impact on their adaptation process. Students who take part in this program tend to have a better level of academic performance compared to those who do not take part in the orientation program. Factors such as social integration, academic knowledge, and psychological support have been shown to play an important role in successful adaptation. Students who take part in the New Student Orientation Program (POMB) experience significant improvements in adapting to the academic environment, create strong social networks, and demonstrate higher motivation. Conclusion The conclusion of this research is that the new student orientation program has an important role in improving their adaptation process and academic performance. Recommendations for improvements to the orientation program may also be identified, such as increased interactive content and increased post-program support to ensure sustainability of positive effects in the long term.